2006
DOI: 10.1080/10428190500463932
|View full text |Cite
|
Sign up to set email alerts
|

Single-agent liposomal all-trans retinoic acid can cure some patients with untreated acute promyelocytic leukemia: an update of The University of Texas M. D. Anderson Cancer Center Series

Abstract: The present study aimed to investigate single-agent liposomal all-trans retinoic acid (Lipo-ATRA) in untreated acute promyelocytic leukemia (APL). Induction therapy consisted of Lipo-ATRA 90 mg/m2 i.v. every other day. Patients in complete remission (CR) continued to receive Lipo-ATRA 90 mg/m2 i.v. three times a week for 9 months. Idarubicin was added only if a polymerase chain reaction test for promyelocytic leukemia-retinoic acid receptor alpha (sensitivity level, 10(-4)), performed every 3 months from CR, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 29 publications
0
30
0
2
Order By: Relevance
“…This, and other evidence, has suggested that RA-induced LIC clearance was the consequence of PML/RARA catabolism, whereas induction of differentiation likely reflected reversal of PML/RARA-dependent transcriptional repression (73). Interestingly, the few patients that were actually cured with RA alone received a liposomal form, which allowed very high and prolonged plasma concentrations (76). Arsenic alone is only a modest inducer of differentiation.…”
Section: Introductionmentioning
confidence: 89%
“…This, and other evidence, has suggested that RA-induced LIC clearance was the consequence of PML/RARA catabolism, whereas induction of differentiation likely reflected reversal of PML/RARA-dependent transcriptional repression (73). Interestingly, the few patients that were actually cured with RA alone received a liposomal form, which allowed very high and prolonged plasma concentrations (76). Arsenic alone is only a modest inducer of differentiation.…”
Section: Introductionmentioning
confidence: 89%
“…Whereas complete differentiation of the leukemia clone is achieved even at low doses of RA, APL clearance (as assessed by survival or loss of clonogenic cells in transplantation assays) correlates almost linearly with the blood RA concentration (J.A., unpublished observations, 2010). This probably explains why, in patients, only liposomal RA, which yields much higher intracellular concentrations than the standard RA oral regimen, has led to some cures as a single agent 42 ( Table 1).…”
Section: Limits Of the Differentiation Paradigmmentioning
confidence: 99%
“…В отношении злокачественно трансформированных клеток в ряде работ показана противоопухолевая активность различных форм витамина А [4,5], в то же время существуют экспериментальные данные, указывающие на опухолестимулирующее влияние ретиноидов [6][7][8]. Это, в первую очередь, результаты исследований опухолестимулирующей активности предшественников витамина А -b-каротина -у лиц с раком лёгких [7].…”
Section: результаты и обсуждениеunclassified
“…Витамин А и его природные и синтетические аналоги -ретиноиды -являются необходимыми факторами для нормального роста, развития и дифференциации [1,2], модулируя экспрессию более 500 генов и участвуя в регуляции пролиферации и апоптоза клеток [3]. В отношении злокачественно трансформированных клеток в ряде работ показана противоопухолевая активность различных форм витамина А [4,5]; в то же время существуют экспериментальные данные, указывающие на опухолестимулирующее влияние ретиноидов [6][7][8]. Опухолевый рост характеризируется высокой метаболической активностью трансформированных клеток и образованием значительных количеств токсических продуктов метаболизма, требующего высокого уровня активности компонентов клеточной системы детоксикации, ведущим элементом которой является микросомальная монооксигеназная система цитохромов Р450 (CYPs) [9].…”
unclassified